Visions of Olonkho : representation of Sakha epic poetry from the 19th century to today - Andreev, Kari Elizabeth (2017)
The genre of heroic epic poetry known as olonkho stands at the forefront of Sakha cultural revival. Its importance has roots in early Soviet nationality policies encouraging ethnic expression and the importance of literary culture in Soviet society. UNESCO’s recognition of olonkho as a “masterpiece of intangible heritage” in 2005 prompted the government of the Sakha Republic to create institutions and policies to promote and preserve it. These institutions engage in debates with performers on the authenticity of contemporary expressions of the epic and how to best ensure that olonkho remains relevant in the lives of Sakha. Olonkho is being integrated into the education of Sakha children as well as being translated for distribution on a global scale. As olonkho solidifies as a signifier for Sakha culture, state sponsorship of the epic indicates support of the expression of Sakha identity in way that resembles early Soviet policies. Current trends indicate that interest in olonkho is growing. Plans for epic-themed projects including the Sakha culture park Olonkholand demonstrate the continuing desire of the Sakha government to invest in the expression of Sakha culture with olonkho at the center. Russian, East European, and Eurasian Studies